Prospects for the introduction of Betula pendula f. dalecarlica (L.F.) C.K. Schneid. in akmolinsk region, Kazakhstan - Saule Mukhtubayeva; Medeu Razhanov; Temirbay Daribay; Zhanna Adamzhanova; Aizhan Zhamangara; Murat Nurushev; Shahizada Akmagambet (Caspian Journal of Environmental Sciences)
The article presents the results of a study of the introduction and prospects for introducing silver birch, Betula pendula f. dalecarlica (L.fil.) Schneid. in the extreme continental climate of the Akmola region, Kazakhstan. Primary tests of rare tree species were conducted based on Astana's Botanical Garden (AstBS). The results of the study indicate the high decorativeness and resistance of this species to adverse environmental influences, what allows recommending this tree planting for urban landscaping, which is considered a promising type of use of its potential in landscape design and gardening, as well as for complex use as part of medicinal gardens. Dalecarlian birch contains a fairly high amount of biologically active substances in leaves and bark. The primary results of tests of the rare tree species, Dalecarlian birch in the Akmola region are presented, which will expand the range of sustainable ornamental species for landscaping cities and towns in the region. Recommendations for further research are given.